Modern Diagnosis and Treatment Technique of Chronic Rhinosinusitis - Jurakulovna, Khushvakova Nilufar; oʻgʻli, Raxmonkulov Umedjon Alisher; oʻgʻli, Moʻminov Akbarali Ikrom; oʻgʻli, Norpulatov Kurbonali Baxriddin; Farxodovich, Samandarov Davron (Journal of Science in Medicine and Life, 2024)
Relevance of the experience: Chronic rhinosinusitis is characterized by a long duration and usually occurs without a significant increase in temperature. The acute condition is always accompanied by high fever, begins unexpectedly and has more pronounced painful symptoms. The main reason for the development of chronic inflammation of the maxillary sinuses is the violation of their normal drainage. It occurs due to long-term infectious or non-infectious swelling (allergy, drug-related swelling) or a violation of mucous membrane clearance in the area of the maxillary nasal anastomosis. Also, the background for the formation of chronic inflammation is anatomical obstacles in the nose that disrupt normal drainage (deviation of the septum, expansion of the middle turbinates).